Polymer-coated graphite material as well as preparation method and application thereof

By coating the surface of the graphite material with polymers such as guar gum, xanthan gum and polyacrylamide, the problem of low efficiency of graphite negative electrode materials for the first time was solved, the battery performance and stability of lithium-ion batteries were improved, and the More efficient battery charging and discharging performance.

CN119275267APending Publication Date: 2025-01-07GAO NENG SHI DAI (SHEN ZHEN) XIN NENG YUAN KE JI YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411380209.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Graphite, as a negative electrode material for sulfide solid-state batteries, has the problem of low Coulomb efficiency for the first time, which has affected the performance of lithium-ion batteries.

Method used

The graphite material coated with polymers is formed by crosslinking polymers with graphite surfaces such as guar gum, xanthan gum, chitosan and polyacrylamide to form a cladding layer, which improves the diffusion capacity of lithium ions and stabilizes the sulfide and The interface between graphite.

Benefits of technology

The first Coulomb efficiency of graphite materials was significantly improved, from 89.12% to 93.10%, and the interface stability between sulfide and graphite was improved, and the cycle stability and safety of the battery were improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275267A_ABST
    Figure CN119275267A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and discloses a polymer-coated graphite material as well as a preparation method and application thereof. The polymer-coated graphite material comprises graphite and a polymer coating layer coating the graphite, the polymer coating layer comprises a component A and a component B; the component A is selected from at least one of guar gum, xanthan gum and chitosan; and the component B is selected from at least one of polyacrylamide and polyaniline. According to the polymer-coated graphite material disclosed by the invention, the components of the polymer coating layer are specifically selected, so that the first coulombic efficiency of the graphite material can be effectively improved, and the interface stability between sulfide and graphite can be maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a polymer-coated graphite material and a preparation method and application thereof. Background Art

[0002] At present, the energy density of traditional liquid lithium-ion batteries is close to the limit, and there is also the safety problem of thermal runaway. Solid-state batteries can achieve an ultra-high energy density of 500Wh / kg, and their electrolytes will not decompose into flammable components, which improves the safety of the battery. Solid-state batteries can be divided into polymer solid-state batteries, oxide solid-state batteries and sulfide solid-state batteries according to the different electrolytes. Among them, sulfide solid electrolytes have ultra-high ionic conductivity and good laminate pressure mechanical properties, making them a current research hotspot.

[0003] Graphite is the most successful negative electrode material in commercialization and has good cycle stability. However, graphite as a negative electrode for sulfide solid-state batteries faces many challenges: lithium ions form a solid electrolyte interface (SEI) during the embedding process of graphite, which consumes a lot of Li + , and the sulfide electrolyte decomposes on the surface of the graphite negative electrode, resulting in low first coulombic efficiency, thus affecting the overall performance of the lithium-ion battery.

[0004] Therefore, there is an urgent need to provide a graphite negative electrode material with improved coulombic efficiency for the first time. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a polymer-coated graphite material and a preparation method and application thereof.

[0006] The present invention proposes a polymer-coated graphite material, which solves the problem of low first coulomb efficiency of graphite materials in the prior art. The polymer in the graphite material of the present invention includes at least one of guar gum, xanthan gum, chitosan, and polyacrylamide (PAM) or polyaniline structure, and at least one of guar gum, xanthan gum, and chitosan has rich -OH functional groups and good lithium conductivity, which can promote the diffusion of lithium ions. The -NH2 functional group contained in the polyacrylamide (PAM) molecule can be connected with the -OH in guar gum (GG) in the form of hydrogen bonds, thereby playing a role in molecular fixation, and in addition, N lone pairs of electrons can also promote the diffusion of lithium ions. The polymer is evenly distributed on the surface of the graphite material, which can effectively improve the first coulomb efficiency of the graphite material and maintain the interface stability between the sulfide and the graphite.

[0007] The first coulombic efficiency is an important parameter of lithium-ion battery performance, because Li + During the embedding process of graphite, a SEI film is formed, which consumes Li +, and a stable SEI can reduce the subsequent Li + The consumption of the electrolyte has a great influence on the battery performance. The present invention can reduce the contact resistance of the electrode and form a dense and stable SEI film by coating a layer of cross-linked polymer on the graphite surface by sol-gel method, thereby improving the first coulomb efficiency of the battery.

[0008] A first aspect of the present invention provides a polymer-coated graphite material.

[0009] Specifically, a polymer-coated graphite material includes graphite and a polymer coating layer coating the graphite;

[0010] The polymer coating layer comprises component A and component B;

[0011] The component A is selected from at least one of guar gum, xanthan gum and chitosan;

[0012] The B component is selected from at least one of polyacrylamide and polyaniline.

[0013] Preferably, the polymer coating layer comprises guar gum and polyacrylamide, which significantly improves the first coulombic efficiency of the graphite material.

[0014] Preferably, the graphite is at least one of natural graphite, mesocarbon microbeads, and composite graphite, and more preferably, mesocarbon microbeads.

[0015] Preferably, the mass ratio of the component A to graphite is 0.1-10:100, more preferably 1-6:100.

[0016] Preferably, the mass ratio of the B component to graphite is 0.1-10:100, more preferably 2-8:100.

[0017] A second aspect of the present invention provides a method for preparing a polymer-coated graphite material.

[0018] Specifically, a method for preparing a polymer-coated graphite material comprises the following steps:

[0019] (1) mixing component A with a solvent to obtain a mixture a, adding graphite to the mixture a and mixing to obtain a suspension b;

[0020] (2) adding component B to suspension b and mixing to obtain suspension c, and reacting to obtain the polymer-coated graphite material;

[0021] The mass of the A component does not exceed 10% of the mass of the graphite; the mass of the B component does not exceed 10% of the mass of the graphite.

[0022] The preparation method of the present invention is a sol-gel method. Guar gum, xanthan gum and chitosan are rich in -OH functional groups, and have lithium-conducting functional groups similar to PEO (polyethylene oxide), which can promote the diffusion of lithium ions; in addition, the -NH2 functional group contained in the polyacrylamide (PAM) or polyaniline molecules can be connected with the -OH in guar gum (GG) in a hydrogen bond, thereby playing a role in molecular fixation, and in addition, the N lone pair of electrons can also promote the diffusion of lithium ions. Therefore, the present invention coats the surface of two polymers and graphite by a sol-gel method, and a uniform coating layer can be achieved and the first coulomb efficiency of the battery can be improved. In addition, this has a good improvement effect on the interface stability between sulfide and graphite.

[0023] Preferably, the mass ratio of the component A to graphite is 0.1-10:100, more preferably 1-6:100.

[0024] Preferably, the mass ratio of the B component to graphite is 0.1-10:100, more preferably 2-8:100.

[0025] Preferably, the solvent is water, for example, deionized water.

[0026] Preferably, the mixing method includes stirring or ultrasonic treatment.

[0027] Preferably, the reaction temperature is 40-80°C, more preferably 50-60°C.

[0028] Preferably, the reaction time is 2-6 hours, more preferably 4-6 hours.

[0029] Preferably, after the reaction is completed, a filtering and / or drying process is further included.

[0030] A third aspect of the present invention provides an application of a polymer-coated graphite material.

[0031] A battery comprises the above polymer-coated graphite material.

[0032] Preferably, the battery includes secondary batteries such as sulfide solid-state batteries and liquid batteries.

[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0034] (1) The polymer-coated graphite material of the present invention can effectively improve the first coulombic efficiency of the graphite material and maintain the interface stability between the sulfide and the graphite by specifically selecting the components of the polymer coating layer.

[0035] (2) The present invention coats a coating layer having lithium conductivity on the graphite surface by a sol-gel method, and the coating layer can effectively improve the first cycle coulombic efficiency of the battery, for example, from 89.12% to 93.10%. The polymer-coated graphite material of the present invention has excellent stability for sulfide solid-state batteries, which is of great significance for realizing sulfide solid-state batteries with good cycle stability and safety, and can also achieve the purpose of reducing costs and increasing efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The charge and discharge curve at 0.1C of the buckle half-cell prepared from mesophase carbon microsphere graphite without any treatment in Comparative Example 3;

[0037] Figure 2 The charge and discharge curves at 0.1C of the button half-cell prepared from the polymer-coated graphite material in Example 1. DETAILED DESCRIPTION

[0038] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0039] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0040] Mesophase carbon microsphere graphite is provided by China Steel Carbon Corporation, and the product model is MG-10.

[0041] Example 1

[0042] A polymer-coated graphite material, comprising graphite and a polymer coating layer coating the graphite;

[0043] The composition of the polymer coating includes guar gum and polyacrylamide;

[0044] The graphite is mesophase carbon microsphere graphite.

[0045] A method for preparing a polymer-coated graphite material comprises the following steps:

[0046] Weigh 0.1 g of guar gum, put it into 50 mL of deionized water, and stir evenly to obtain a mixture a;

[0047] Weigh 9.6 g of mesocarbon microsphere graphite and slowly add it into mixture a, stirring at 600 rpm to form a uniform suspension b;

[0048] Weigh 0.3 g of polyacrylamide, place it in 20 mL of deionized water, stir it evenly, and add it dropwise into suspension b to obtain suspension c, and react at 50° C. for 4 h;

[0049] The product obtained by the above reaction is filtered to obtain a filter cake d;

[0050] The filter cake d was dried in a vacuum oven at 80° C. for 12 h to obtain a polymer-coated graphite material.

[0051] Example 2

[0052] A method for preparing a polymer-coated graphite material comprises the following steps:

[0053] Weigh 0.1 g of xanthan gum, put it into 50 mL of deionized water, and stir evenly to obtain a mixture a;

[0054] Weigh 9.6 g of mesocarbon microsphere graphite and slowly add it into mixture a, stirring at 600 rpm to form a uniform suspension b;

[0055] Weigh 0.3 g of polyacrylamide, place it in 20 mL of deionized water, stir it evenly, and add it dropwise into suspension b to obtain suspension c, and react at 50° C. for 4 h;

[0056] The product obtained by the above reaction is filtered to obtain a filter cake d;

[0057] The filter cake d was dried in a vacuum oven at 80° C. for 12 h to obtain a polymer-coated graphite material.

[0058] Example 3

[0059] A method for preparing a polymer-coated graphite material comprises the following steps:

[0060] Weigh 0.1 g of guar gum, put it into 50 mL of deionized water, and stir evenly to obtain a mixture a;

[0061] Weigh 9.6 g of mesocarbon microsphere graphite and slowly add it into mixture a, stirring at 600 rpm to form a uniform suspension b;

[0062] Weigh 0.3 g of polyaniline, place it in 20 mL of deionized water, stir it evenly, and add it dropwise into suspension b to obtain suspension c, and react at 50° C. for 4 h;

[0063] The product obtained by the above reaction is filtered to obtain a filter cake d;

[0064] The filter cake d was dried in a vacuum oven at 80° C. for 12 h to obtain a polymer-coated graphite material.

[0065] Example 4

[0066] A method for preparing a polymer-coated graphite material comprises the following steps:

[0067] Weigh 0.1 g of guar gum, put it into 50 mL of deionized water, and stir evenly to obtain a mixture a;

[0068] Weigh 9.6 g of natural graphite and slowly add it into mixture a, stirring at 600 rpm to form a uniform suspension b;

[0069] Weigh 0.3 g of polyacrylamide, place it in 20 mL of deionized water, stir it evenly, and add it dropwise into suspension b to obtain suspension c, and react at 50° C. for 4 h;

[0070] The product obtained by the above reaction is filtered to obtain a filter cake d;

[0071] The filter cake d was dried in a vacuum oven at 80° C. for 12 h to obtain a polymer-coated graphite material.

[0072] Example 5

[0073] A method for preparing a polymer-coated graphite material comprises the following steps:

[0074] Weigh 0.1 g of xanthan gum, put it into 50 mL of deionized water, and stir evenly to obtain a mixture a;

[0075] Weigh 9.8 g of mesocarbon microsphere graphite and slowly add it into mixture a, stirring at 600 rpm to form a uniform suspension b;

[0076] Weigh 0.1 g of polyacrylamide, place it in 20 mL of deionized water, stir it evenly, and add it dropwise into suspension b to obtain suspension c, and react at 50°C for 4 h;

[0077] The product obtained by the above reaction is filtered to obtain a filter cake d;

[0078] The filter cake d was dried in a vacuum oven at 80° C. for 12 h to obtain a polymer-coated graphite material.

[0079] Comparative Example 1

[0080] Compared with Example 1, the difference of Comparative Example 1 is that the guar gum in Example 1 is replaced by an equal amount of polyethylene glycol, and the other processes are the same as those in Example 1.

[0081] Comparative Example 2

[0082] Compared with Example 1, the difference of Comparative Example 2 is that the polyacrylamide in Example 1 is replaced by an equal amount of polyethyleneimine, and the other processes are the same as those in Example 1.

[0083] Comparative Example 3

[0084] Comparative Example 3 is mesophase carbon microsphere graphite without any treatment.

[0085] Comparative Example 4

[0086] A method for preparing a polymer-coated graphite material comprises the following steps:

[0087] Weigh 1.0 g of guar gum, put it into 50 mL of deionized water, and stir evenly to obtain a mixture a;

[0088] Weigh 8.0 g of mesocarbon microsphere graphite and slowly add it into mixture a, stirring at 600 rpm to form a uniform suspension b;

[0089] Weigh 1.0 g of polyacrylamide, place it in 20 mL of deionized water, stir it evenly, and add it dropwise into suspension b to obtain suspension c, and react at 50° C. for 4 h;

[0090] The product obtained by the above reaction is filtered to obtain a filter cake d;

[0091] The filter cake d was dried in a vacuum oven at 80° C. for 12 h to obtain a polymer-coated graphite material.

[0092] Product effect testing

[0093] The polymer-coated graphite materials prepared in the above comparative examples and embodiments were tested for the first coulombic efficiency and rate performance at different current densities.

[0094] The method for preparing a battery using the above-mentioned polymer-coated graphite material is as follows: grind the polymer-coated graphite material together with the electrolyte LiP6S5Cl, and then add the binder PTFE (polytetrafluoroethylene), wherein the mass ratio of the polymer-coated graphite material, the electrolyte LiP6S5Cl, and the binder PTFE is 60:40:1, and then grind evenly again and cut into 8mm diameter discs, put them into a mold, add the electrolyte LiP6S5Cl, and the counter electrode is a Li-In alloy. The whole is pressed at a pressure of 450MPa to obtain an electrode sheet. When assembling a button battery, stainless steel gaskets are added on both sides of the electrode sheet, and a nickel mesh shrapnel is added on one side for packaging to obtain a button battery. The test pressure is 5MPa. The charge and discharge range is -0.61 to 1.5V, and the first cycle charge and discharge test is carried out at 0.1C. The test results are shown in Table 1.

[0095] Table 1

[0096]

[0097]

[0098] As can be seen from Table 1, the first coulombic efficiency of the polymer-coated graphite materials prepared in Examples 1 to 5 of the present invention is significantly higher than that of Comparative Examples 1 to 4. It can be seen that when the type and amount of component A and component B of the present invention are changed, the first coulombic efficiency of the obtained polymer-coated graphite material will decrease, which shows that the present invention is selective for the type and amount of component A and component B, and the selectivity can achieve unexpected technical effects.

[0099] Figure 1 The charge and discharge curve at 0.1C of the buckle half-cell prepared from mesophase carbon microsphere graphite without any treatment in Comparative Example 3; Figure 2 The charge and discharge curves at 0.1C of the button half-cell prepared from the polymer-coated graphite material in Example 1.

[0100] from Figure 1 It can be seen that in the untreated mesophase carbon microsphere graphite negative electrode, a hump appears near 0.5V during the graphite lithium embedding process. This is the process of forming the SEI film and the decomposition of the sulfide electrolyte, which generates substances such as Li3P, resulting in a phenomenon in which the voltage first decreases and then increases. At this time, all the reactions that occur before the lithium ions are embedded in the graphite are side reactions, with a capacity loss of about 46mAh / g, so the first coulomb efficiency is only 89.12%.

[0101] from Figure 2 It can be seen that the hump near 0.5V disappears, but a small amount of side reactions occur, which is the formation of SEI. Before lithium insertion, the polymer-coated graphite material reduces the capacity loss to 33mAh / g. The lithium loss is reduced and the side reactions are reduced, so the first coulombic efficiency of the battery can be increased to 93.10%.

Claims

1. A polymer-coated graphite material, characterized in that: comprising graphite and a polymer coating layer coating the graphite; The polymer coating layer comprises component A and component B; The component A is selected from at least one of guar gum, xanthan gum and chitosan; The B component is selected from at least one of polyacrylamide and polyaniline.

2. The polymer-coated graphite material according to claim 1, characterized in that: The polymer coating layer comprises guar gum and polyacrylamide.

3. The polymer-coated graphite material according to claim 1, characterized in that: The graphite is at least one of natural graphite, mesophase carbon microspheres and composite graphite.

4. The polymer-coated graphite material according to claim 1, characterized in that: The mass ratio of the A component to graphite is 0.1-10:

100.

5. The polymer-coated graphite material according to claim 1, characterized in that: The mass ratio of the B component to graphite is 0.1-10:

100.

6. The method for preparing the polymer-coated graphite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing component A with a solvent to obtain a mixture a, adding graphite to the mixture a and mixing to obtain a suspension b; (2) adding component B to suspension b and mixing to obtain suspension c, and reacting to obtain the polymer-coated graphite material; The mass of the A component does not exceed 10% of the mass of the graphite; the mass of the B component does not exceed 10% of the mass of the graphite.

7. The preparation method according to claim 6, characterized in that: The solvent is water; and / or the mixing method includes stirring or ultrasonic treatment.

8. The preparation method according to claim 6, characterized in that: The reaction temperature is 40-80° C.; and / or the reaction time is 2-6 hours.

9. The preparation method according to claim 6, characterized in that: After the reaction is completed, the process further includes filtering and / or drying.

10. A battery, characterized in that: The invention comprises the polymer-coated graphite material according to any one of claims 1 to 5.